2007
DOI: 10.1097/01.anes.0000286980.92759.94
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Equiosmolar Solutions of Mannitol versus  Hypertonic Saline on Intraoperative Brain Relaxation and Electrolyte Balance

Abstract: Mannitol and HS cause an increase in cerebrospinal fluid osmolality, and are associated with similar brain relaxation scores and arteriovenous oxygen and lactate difference during craniotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
93
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(105 citation statements)
references
References 32 publications
(22 reference statements)
7
93
2
1
Order By: Relevance
“…In line with previous reports [9,35,39,40], our SR confirmed that the administration of HTS heightened the levels of serum sodium, which was sustained for 6 h, and promoted a temporary reduction of potassium [20-22, 24, 26]. In contrast, mannitol caused a transient acute dilutional hyponatremia [20,22,26], with a concomitant stepwise increase of potassium over time [22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with previous reports [9,35,39,40], our SR confirmed that the administration of HTS heightened the levels of serum sodium, which was sustained for 6 h, and promoted a temporary reduction of potassium [20-22, 24, 26]. In contrast, mannitol caused a transient acute dilutional hyponatremia [20,22,26], with a concomitant stepwise increase of potassium over time [22].…”
Section: Discussionsupporting
confidence: 92%
“…While all hyperosmolar agents promote diuresis, HTS exerts a weaker diuretic effect than mannitol, possibly because it stimulates the release of antidiuretic hormones [9,39,40]. By contrast, mannitol infusion could induce hypovolaemia through an increase in diuresis [13,[20][21][22][23][24][25]28].…”
Section: Discussionmentioning
confidence: 99%
“…Using a cerebral relaxation scale similar to the one we used, Gemma et al 9 reported satisfactory cerebral relaxation in all cases when different osmolar loads but similar volume of HS (7.5%) or mannitol (20%) were administered. On the other hand, Rozet et al 10 observed a similar effect on cerebral relaxation when equiosmolar solutions of mannitol and HS were used. The main mechanism of action of hyperosmolar solutions is the generation of an osmolar gradient across the blood brain barrier (BBB), due to its impermeability to solutes (sodium and mannitol) 10 , leading to contraction of cerebral tissue (were the BBB is intact) and therefore reducing the ICP.…”
Section: Discussionmentioning
confidence: 86%
“…During craniotomy, mannitol is frequently used to facilitate brain relaxation primarily via the reduction of brain tissue water (29, 30). However, mannitol is also an osmotic diuretic, its use leads to a large urine output and intravascular volume depletion as a consequence (31). Whether the depleted volume should be replaced is debated.…”
Section: Optimizing Intravascular Volume and Monitoring Cardiac Outpumentioning
confidence: 99%